Elucidating the Interplay between Non‐Stoquasticity and the Sign Problem. Issue 1 (27th November 2019) - Gupta, Lalit; Hen, Itay
Abstract: The sign problem is a key challenge in computational physics, encapsulating the inability to properly understand many important quantum many‐body phenomena in physics, chemistry, and the material sciences. Despite its centrality, the circumstances under which the problem arises or can be resolved as well as its interplay with the related notion of "non‐stoquasticity" are often not very well understood. In this study, an attempt is made to elucidate the circumstances under which the sign problem emerges and to clear up some of the confusion surrounding this intricate computational phenomenon. To that aim, the recently introduced off‐diagonal series expansion quantum Monte Carlo scheme is used to analyze in detail a number of examples that capture the essence of the results. Abstract : In this study, the circumstances under which the sign problem emerges are elucidated and its interplay with the related notion of non‐stoquasticity is examined in detail. To that aim, the recently introduced off‐diagonal series expansion quantum Monte Carlo scheme is used to analyze in detail a number of examples that capture the essence of the results.